A Spatial Reading of Obadiah on the Vertical Axis of the Ancient Near Eastern Cosmic Geography: Festschrift for GTM Prinsloo - Schäder, Jo-Marí (Journal for Semitics, 2023)
Since the 1970s, biblical studies have experienced a “spatial turn,” giving rise to an emphasis on a variety of approaches to the spatial analysis of biblical texts. Space is something that is constructed, produced, and represented by means of words. It is thus possible for the associations and memories of spaces to change. This study’s purpose is threefold: (1) to provide a short overview of the significance of studying space and memory together; (2) to provide an overview of ancient Near Eastern cosmic geography to contextualise our study’s reference to vertical spatial orientation; and (3) to illustrate how such a vertical spatial reading can aid us in better understanding the text of Obadiah, which deals predominantly with space in terms of land and sacred space.